A novel technique to neutralize the Yawing moment due to asymmetric thrust in a hybrid buoyant aircraft - Haque, Anwar Ul; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Mohamed Ali, Jaffar Syed (EDP Sciences, 2016)
Dorsal fin is used in swimming animals like shark for the generation of thrust as well as to meet the requirement of the lateral stability. In the case of aircraft, rudders are normally used for the said requirement. In the present work, this nature inspired idea is explored for its application to neutralize the unavoidable asymmetric thrust produced by the twin engines of a hybrid buoyant aircraft. First, the estimation of asymmetric thrust is obtained with the help of analytical techniques for maximum thrust condition at 4 degree angle of attack. The moment generated by it is utilized for the sizing of a dorsal fin which looks similar to a tapered wing and is placed aft of the center of gravity. Wind tunnel testing at subsonic speed is carried out to explore the design features of this rotatable dorsal fin. It is found that a small rotation of 5 degree can generate the required moment. However, such rotation requires a complete pneumatic/electro-mechanical system and an alternative of it is to use a cambered airfoil for the dorsal fin installed at fixed location. Such a flow controlling device can also be used as an antenna mast, which is commonly installed out the fuselage of the aircraft for communication purposes. Moreover, by incorporating this technique, a pilot doesn't have to put an extra effort to make the aircraft stable in the presence of side wind.